Where Two Worlds Meet - Living History and Heritage Locations - Luc Eekhout (EXARC Journal)
The Netherlands have an abundance of heritage locations: museums, monuments, windmills. A favorite pastime of many senior citizens is to take responsibility for this heritage as volunteer guides, amateur historians, and so on. Their traditional contribution to the Dutch heritage sector is tremendous. But at the same time there is a trend of aging in this kind of volunteering. The provincial ‘Heritage Houses’ – a professional platform for archives, museums, windmills etc. – are alarmed at the potential threat of a shortage of volunteers.